METODE PARTISIPATIF, CERAMAH, DAN DISKUSI PADA AL QUR’AN SURAT AS-SHAFFAT AYAT 102 - Nini; Zulvia Trinova; Afdal Fauzen (Paedagogia: Jurnal Pendidikan, 2019)
This research is motivated by a phenomenon of poor communication between parents and children. In the world of education, there was a lack of approaches and methods used by educators in providing subject matter so that what was delivered by the educator did not achieve the expected goals. The problem in this research is how the participatory methods, lectures and discussions contained in the As-Shaffat letter verse 102. The purpose is to describe the educational methods contained in the As-Shaffat letter verse 102 in the form of participatory methods, lecture methods and discussion methods. This research is a Library Research. The method of interpretation used in this study is the method of interpretation of maudhu 'or thematic methods which interpret verses of the Qur'an based on specific themes. The method used in the explanation of the verse is the method of tahlili or analysis that explains the verses of the Qur'an by examining its aspects and revealing its whole purpose. The results of study and analysis, as well as data processing from various sources, obtained the first result that the educational method contained in the As-Shaffat verse 102 is a participatory method used by educators, which involves all elements in the educational process especially students, with active participation from participants students will facilitate educators in delivering the material to be given. Both lecture methods, in conveying information, especially learning materials can be done with the lecture method. An educator prioritizes good attitudes so that the material can be accepted by students. The third method of discussion is to involve students in giving their opinions. With the discussion in learning, the lessons will become warmer and will train students to be more courageous in opinion.